Forms of Illocutionary Speech Acts on Deddy Corbuzier’s Podcast - Rettob, Fifi; Pesiwarissa, Leonora Farilyn; Lelapary, Heppy Leunard (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the form of illocutionary speech acts in the Deddy Corbuzier Podcast. The problem studied is the form of illocutionary speech acts in the Deddy Corbuzier Podcast. This type of research is descriptive qualitative. The data in this research are the words of Deddy Corbuzier's Podcast in the episode "I'm Crying, Behind Their Laughter It Turns Out Everything Is Sold to Survive - The Life Fate of Kadir and Doyok". This verbal data is then transcribed into written data for analysis. The data source in this research is the YouTube video on the Deddy Corbuzier Podcast. Data collection techniques in this research are: recording technique, listening technique, and note-taking technique. After collecting data, the data analysis techniques used are data reduction, data presentation, drawing conclusions. The research results show four forms of illocutionary speech acts in the Deddy Corbuzier Podcast. First, assertive speech acts are used to explain something as it is, directive speech acts are used speech acts that produce many effects or influence through the listener's actions, expressive speech acts are speech acts that involve feelings and attitudes.